Effects of Structural Inequalities and Misleading Discourse of Social Policymakers on African American families in God Help the Child (Journal of Social Sciences Review, 2023)
In sociological and anthropological studies of African American family formation and development, racial hierarchies, criminal violence, social policies, and systemic disparities are often ignored. This study emphasizes the gradual development of consequences of xenophobic attitude of the society that stigmatizes African American family culture in the United States. The prevalent approach in social sciences was to blame the victim on certain group membership or racial specification such as color, background, and physical traits. These structural inconsistencies have been undervalued or studied only occasionally and irregularly. This is qualitative study that analysis Toni Morrison’s Gold Help the Child in the light of a rethinking history, a postmodern notion. The textual analysis of the selected text reveals that that formative policy makers focused on Black people’s violence and individual level incongruities but ignored their fundamental problems and latent potentialities. The finding further shows that the lack of structural and systematic analysis misled the discourse of policy makers and more precisely often justified black violence that reflects cultural inferiority and unique experiences of legitimatizing all kinds of violence and negativity propogated against them.
Keywords: Policy; Reformative; Rethinking; Segregation; Bondages; Disintegrated; Family and Structure